2022
DOI: 10.1007/s12079-022-00691-1
|View full text |Cite
|
Sign up to set email alerts
|

SHP2 regulates adipose maintenance and adipocyte-pancreatic cancer cell crosstalk via PDHA1

Abstract: Adipocytes are the most abundant cell type in the adipose tissue, and their dysfunction is a significant driver of obesity-related pathologies, such as cancer. The mechanisms that (1) drive the maintenance and secretory activity of adipocytes and (2) mediate the cancer cellular response to the adipocyte-derived factors are not fully understood. To address that gap of knowledge, we investigated how alterations in Src homology region 2-containing protein (SHP2) activity affect adipocyte function and tumor crosst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 69 publications
(116 reference statements)
0
2
0
Order By: Relevance
“…First, Deng et al revealed that it could represent a prognostic and immune-associated biomarker in multiple cancers, its expression being linked to DNA damage, cell invasion, and angiogenesis [26]. A second study by Olou et al pointed to its involvement in adipocyte maintenance and secretion of the cancer-promoting cytokine IL-6 [27]. Finally, Tian et al showed that silencing this gene suppressed proliferation, migration, and invasion in neuroblastoma [28].…”
Section: Discussionmentioning
confidence: 99%
“…First, Deng et al revealed that it could represent a prognostic and immune-associated biomarker in multiple cancers, its expression being linked to DNA damage, cell invasion, and angiogenesis [26]. A second study by Olou et al pointed to its involvement in adipocyte maintenance and secretion of the cancer-promoting cytokine IL-6 [27]. Finally, Tian et al showed that silencing this gene suppressed proliferation, migration, and invasion in neuroblastoma [28].…”
Section: Discussionmentioning
confidence: 99%
“…Fedele et al (95) discovered that SHP2 inhibition reduced RTK feedback signals and enhanced the action of KRAS G12C inhibitors in PDAC. Furthermore, the SHP2-PDHA1-ROS axis is crucial for the upkeep of adipocytes and may regulate cytokine production as well as the proliferation of pancreatic cancer cells (96). Consequently, the majority of recent research points to a favorable association between SHP2 and the onset and progression of PDAC, indicating that SHP2 might be a desirable target in treatment combinations for this predominantly KRASmutated entity.…”
Section: Pancreatic Ductal Adenocarcinomamentioning
confidence: 99%
“…Some evidence suggested PDHA1 was closely related to the progression and prognosis of gastric, pancreatic and esophageal squamous cancer (31)(32)(33). Therefore, we performed Kaplan-Meier analysis between CRGs expression and survival outcomes in BC, including OS and RFS.…”
Section: Crgs Prognostic Value In Bcmentioning
confidence: 99%